Harmonising Accessibility in the EU Single Market: Challenges for Making the European Accessibility Act Work - Drabarz, Anna Katarzyna (Review of European and Comparative Law, 2020)
In the last decade, accessibility has become a buzzword not only among actors of the civil society advocating for the rights of persons with disabilities but also among the legislators in the European Union. The EU has adopted a series of binding regulations aiming at approximating the common understanding of accessibility and Member States’ approach to operationalising the right. Being part of EU harmonised law, the European Accessibility Act has already been considered a milestone in the process. The choice of an approach / approaches will decide about a success of its transposition into Member States legal systems.